2018
DOI: 10.5539/ibr.v11n11p55
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the Impact of Managerial Ownership on the Performance of Shariah-Compliant Firms in Pakistan

Abstract: This paper analyses the impact of managerial ownership upon firm performance in the Shariah-compliant firms of Pakistan. Agency theory that suggests involving managers as part of firm's ownership can help firms reduce the agency cost, has widely been applied in the corporate setup of conventional finance, however, there is growing need of academic research to find out the role and application of this theory in the Shariah-compliant organizations. All around the Muslim world, there is the rise of Sharia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 43 publications
3
9
1
Order By: Relevance
“…Mahrani & Soewarno, (2018), Ahmad et al, (2019) H2: Institutional ownership positively affects financial performance GCG through the management ownership mechanism has a good impact on the company performance, because it can increase management's motivation to continue to work better and be careful in every decision-making activity so that it will not harm the company, and an increase in company profits makes managers feel they have the right to these profits, and this is in line with agency theory, namely the interests that occur in agents and company owners will establish good relationship to improve financial performance (Tertius & Christiawan, 2015). Research by Anželika et al, (2017), Katper et al, (2018), Irawati et al, (2019), Novitasari et al, (2020), and Hermawan et al, (2021) showed significant positive results. H3: Managerial ownership positively affects financial performance Nawangwulan, (2019) explained that liquidity is a condition of company will be considered in good condition if it is able to pay off its short-term debt, this is related to the firm size, namely the large companies will be relatively more stable and able to face uncertanty because they have a higher amount of assets, and then are able to strengthen the influence of liquidity on the financial performance.…”
Section: Relationships Between Variablesmentioning
confidence: 92%
See 1 more Smart Citation
“…Mahrani & Soewarno, (2018), Ahmad et al, (2019) H2: Institutional ownership positively affects financial performance GCG through the management ownership mechanism has a good impact on the company performance, because it can increase management's motivation to continue to work better and be careful in every decision-making activity so that it will not harm the company, and an increase in company profits makes managers feel they have the right to these profits, and this is in line with agency theory, namely the interests that occur in agents and company owners will establish good relationship to improve financial performance (Tertius & Christiawan, 2015). Research by Anželika et al, (2017), Katper et al, (2018), Irawati et al, (2019), Novitasari et al, (2020), and Hermawan et al, (2021) showed significant positive results. H3: Managerial ownership positively affects financial performance Nawangwulan, (2019) explained that liquidity is a condition of company will be considered in good condition if it is able to pay off its short-term debt, this is related to the firm size, namely the large companies will be relatively more stable and able to face uncertanty because they have a higher amount of assets, and then are able to strengthen the influence of liquidity on the financial performance.…”
Section: Relationships Between Variablesmentioning
confidence: 92%
“…Anželika et al, (2017) show a significant positive influence GCG with the mechanism of ownership structure on Article's contents are provided on a Attribution-Non Commercial 4.0 Creative commons license. To see the complete license contents, please visit http://creativecommons.org/licenses/by-nc/4.0/ financial performance, and supported by Katper et al, (2018), Mahrani & Soewarno, (2018), Ahmad et al, (2019), Arianpoor, (2019, Irawati et al, (2019), Panda & Leepsa, (2019), Suryanto & Refianto, 2019, Hindasah et al, (2020), Novitasari et al, (2020), Setiawan & Setiadi, (2020), Sakawa & Watanabel, (2020), Hermawan et al, (2021) and Sofiana et al, (2022). Meanwhile the negative influence shown by Elisetiawati & Artinah, (2016), Saidu et al, (2018), Tsouknidis, (2019), and Sani, (2020.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies examine the insider ownership-performance relationship and find mixed results. Some studies find positive relation (Kaserer & Moldenhauer, 2008;Hu & Zhou, 2008;Katper et al, 2018), few studies observe negative (Fahlenbrach & Stulz, 2008;Shah et al, 2011;Ali et al, 2020;Vintilă & Gherghina, 2015). Yet some others find no relationship (Demsetz & Lehn, 1985;Abdullah et al, 2011;Hamza & Suman, 2018).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 98%
“…Inside shareholdings align the insiders' interests with those of minority shareholders, helping control the agency problem. A substantial ownership stake of the insiders 1 It motivates them to monitor firm because of the "incentives effect" and contributes to increased performance (Jensen, 1986;Kamardin, 2014;Katper et al, 2018). It discourages the insiders' motivation in tunnelling firm's assets by various channels, including inside trading, transfer pricing, in-efficient or over-investment, employing incompetent management and excessive perquisites (Djankov et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Increased demand for Shariah -compliant products has also resulted in considerable amount of academic research (Farooq, 2014; Farooq and AbdelBari, 2015; Farooq and Alahkam, 2016). Most of this research is, however, concentrated on the issues related to risk and return of Shariah -compliant assets (Alam and Rajjaque, 2016; Katper et al , 2018; Hassan et al , 2018). An important question that has received insufficient attention in prior literature is related to the information transmission capacity of stock prices of Shariah -compliant firms.…”
Section: Introductionmentioning
confidence: 99%